Effects of the pSC101 partition (par) locus on in vivo DNA supercoiling near the plasmid replication origin. - Conley, D L (1995)
Previous work has shown that deletion of the partition (par) locus of plasmid pSC101 results in decreased overall superhelical density of plasmid DNA and concommitant inability of the plasmid to be stably inherited in populations of dividing cells. We report here that the biological effects of par correlate specifically with its ability to generate supercoils in vivo near the origin of pSC101 DNA replication. Using OsO4 reactivity of nucleotides adjoining 20 bp (G-C) tracts introduced into pSC101 DNA to measure local DNA supercoiling, we found that the wild type par locus generates supercoiling near the plasmid's replication origin adequate to convert a (G-C) tract in the region to Z form DNA. A 4 bp deletion that decreases par function, but produces no change in the overall superhelicity of pSC101 DNA as determined by chloroquine/agarose gel analysis, nevertheless reduced (G-C) tract supercoiling sufficiently to eliminate OsO4 reactivity. Mutation of the bacterial topA gene, which results in stabilized inheritance of par-deleted plasmids, restored supercoiling of (G-C) tracts in these plasmids and increased OsO4 reactivity in par+ replicons. Removal of par to a site more distant from the origin decreased supercoiling in a (G-C) tract adjacent to the origin and diminished par function. Collectively, these findings indicate that par activity is dependent on its ability to produce supercoiling at the replication origin rather than on the overall superhelical density of the plasmid DNA.